2017
DOI: 10.1002/wow3.93
|View full text |Cite
|
Sign up to set email alerts
|

Global employment and social trends

Abstract: Against the backdrop of a rather disappointing economic performance in 2016 and the below‐trend outlook for 2017, Chapter 1 assesses the ability of the economy to (i) generate a sufficient number of jobs, (ii) improve the quality of employment for those with a job, and (iii) ensure that the gains of growth are shared in an inclusive manner. The chapter also discusses the policy efforts needed to overcome structural impediments to growth, including inequality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(9 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Our study showed the higher probability of facing a barrier due to exams' costs for females and people with a low income, in agreement with the other literature [34]. Regarding gender gaps, it can be viewed as the result of gender differences in the Italian labor market [35]. It is well documented that on average, women earn 14.1% less per hour than men for the same position and seniority, show higher unemployment rates (20%), and have high-skilled and highly paid employment that is less than men [36,37].…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed the higher probability of facing a barrier due to exams' costs for females and people with a low income, in agreement with the other literature [34]. Regarding gender gaps, it can be viewed as the result of gender differences in the Italian labor market [35]. It is well documented that on average, women earn 14.1% less per hour than men for the same position and seniority, show higher unemployment rates (20%), and have high-skilled and highly paid employment that is less than men [36,37].…”
Section: Discussionsupporting
confidence: 91%
“…With more than half the global population currently employed, occupational exposures are of great public health importance (Kühn, 2019). Heat exposures occur frequently in many occupations, including in both indoor and outdoor workers such as chefs, factory workers, and farmers (NIOSH, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…of women's economic engagement. A report by the International Labor Organization (ILO) finds that limited access to safe transportation is likely to reduce female labour force participation rate in developing countries by 16.5 percentage points (Kühn et al 2017). Other studies have highlighted the effect of sex differences in household "roles" in influencing women to work "closer to home" (Fanning 1981).…”
Section: Introductionmentioning
confidence: 99%